Do you believe that atoms stay in place when you observe them in HREM?. (January 2015) - Van Dyck, Dirk; Lobato, Ivan; Chen, Fu-Rong; Kisielowski, Christian
Highlights: Unexpectedly large atom displacements are explained which are found to be dose-rate dependent. Electron beam-induced object excitation and relaxation contribute to the imaging process. Large atom displacements in HREM are explained by dose-rate dependent thermal diffuse scattering. Abstract: Recent advancements in aberration-corrected electron microscopy allow for an evaluation of unexpectedly large atom displacements beyond a resolution limit of ∼0.5 Å, which are found to be dose-rate dependent in high resolution images. In this paper we outline a consistent description of the electron scattering process, which explains these unexpected phenomena. Our approach links thermal diffuse scattering to electron beam-induced object excitation and relaxation processes, which strongly contribute to the image formation process. The effect can provide an explanation for the well-known contrast mismatch ("Stobbs factor") between image calculations and experiments.